Everything belongs : the gift of contemplative prayer - Rohr, Richard (New York : Crossroad, 2003)
["This popular and bestselling book of the renowned Franciscan challenges people to move beyond the comfort of a settled life toward an understanding of themselves that is rooted in their connection to God."]
Guide for reflection.
Keywords: Contemplation; Spiritual life -- Catholic Church